2018
DOI: 10.1515/mammalia-2017-0163
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive age estimation in rodents by measuring incisors width, with the Zaisan mole vole (Ellobius tancrei) as an example

Abstract: Non-invasive age estimation is critically important for many field studies but often it represents a significant challenge. In rodents, upper incisors represent a part of a cranium which can be readily measured in an alive animal. We propose an age estimation method based on the measurements of both upper incisors’ width (IW) for a subterranean rodent,Ellobius tancrei. The IW measurements for 77 laboratory-born females and 81 males were fitted, separately for the sexes, by sigmoidal Gompertz growth functions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…4b), therefore giving an estimated Age for a given tusk Radius. A similar power cascade pattern is found in the incisors of the Zaisan mole vole Ellobius tancrei [30] during juvenile growth (Fig. 4c) but at a much smaller scale.…”
Section: Power Cascade Model Can Predict Tooth Length and Agesupporting
confidence: 76%
See 1 more Smart Citation
“…4b), therefore giving an estimated Age for a given tusk Radius. A similar power cascade pattern is found in the incisors of the Zaisan mole vole Ellobius tancrei [30] during juvenile growth (Fig. 4c) but at a much smaller scale.…”
Section: Power Cascade Model Can Predict Tooth Length and Agesupporting
confidence: 76%
“…4 c) but at a much smaller scale. While incisor circumference or width have been used to estimate age previously based solely on regression [ 30 , 31 ], the power cascade describes the underlying pattern, and allows for estimation of age from growth parameters alone. Additional work on the limitations and accuracy of predictions derived from this approach is currently underway.…”
Section: Resultsmentioning
confidence: 99%
“…obs.). For Zaisan mole voles ( Ellobius tancrei ), a subterranean murid species with bathyergid-like extrabuccal incisors, it has already been demonstrated that incisor width can act as an age marker well into adulthood, before values for different age cohorts will eventually converge 60 . At what age incisor width becomes uninformative to differentiate breeding males from younger non-breeders in Fukomys remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…)values for different age cohorts will eventually converge60 . At what age incisor width becomes uninformative to differentiate breeding males from younger non-breeders in Fukomys remains to be determined.…”
mentioning
confidence: 91%
“…obs.). For Zaisan mole voles ( Ellobius tancrei ), a subterranean murid species with bathyergid-like extrabuccal incisors, it has already been demonstrated that incisor width can act as an age marker well into adulthood in both sexes, before values for different age cohorts will eventually converge (Kuprina & Smorkatcheva, 2019). At what age incisor width becomes uninformative to differentiate breeding males from younger non-breeders in Fukomys remains to be determined.…”
Section: Discussionmentioning
confidence: 99%